2010
DOI: 10.1007/s10461-010-9778-9
|View full text |Cite
|
Sign up to set email alerts
|

Persons Newly Diagnosed with HIV Infection are at High Risk for Depression and Poor Linkage to Care: Results from the Steps Study

Abstract: Little is known about the prevalence and impact of depression in persons newly diagnosed with HIV infection. The Steps Study is a prospective, observational cohort study of persons newly diagnosed with HIV infection. Participants were administered a battery of instruments, including the CES-D. Linkage to care was defined as attending at least one clinic appointment in each of the first two 90-day intervals following diagnosis. Of 180 participants, 67% screened positive for depression. In multivariate analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 54 publications
7
126
1
3
Order By: Relevance
“…In another Indian study, 20 prevalence rates of depression among HIV sero-positive individuals were ranged from 10% to 40%. In similar studies, Kaharuza et al 21 and Bhatia et al 22 found prevalence of depression to be 47% in Uganda and 45% in USA respectively. Collaborating with these reports, our findings point out that depression could be relatively frequent among HIV/AIDS patients.…”
Section: Discussionmentioning
confidence: 78%
“…In another Indian study, 20 prevalence rates of depression among HIV sero-positive individuals were ranged from 10% to 40%. In similar studies, Kaharuza et al 21 and Bhatia et al 22 found prevalence of depression to be 47% in Uganda and 45% in USA respectively. Collaborating with these reports, our findings point out that depression could be relatively frequent among HIV/AIDS patients.…”
Section: Discussionmentioning
confidence: 78%
“…Depression is common following a diagnosis of HIV and may be worse in areas with high levels of stigma. [14][15] Depression is associated with both reduced linkage to care and impaired adherence to ART, 16 but can be effectively treated with interpersonal support group therapy. 17 The formation of community support groups of patients who have disclosed their HIV status to the group may prevent depression and improve retention in care in newly diagnosed patients.…”
Section: How Should We Care For Patients Who Are Not Yet Eligible Formentioning
confidence: 99%
“…age, sex or gender, income, immigration status) [6][7][8][9][10][11][12], psychosocial factors (e.g. mental health status, substance use, homelessness) [13][14][15], and geographic factors (e.g. rural or remote residence) [16].…”
Section: Introductionmentioning
confidence: 99%
“…rural or remote residence) [16]. Conversely, people are more likely to present to care if they are employed [13].…”
Section: Introductionmentioning
confidence: 99%